The impact of extreme weather events on child health: Evidence from Mongolia - Kati Schindler; Valeria Groppo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper investigates the impact of a devastating weather shock on child anthropometrics, using data from Mongolia. We employ a diff-in-diff strategy to identify the effect of an extremely harsh winter in 2010, which caused the death of about 20 percent of the national livestock. Results indicate that cohorts of children exposed to the 2010 winter and who lived in districts in which the shock was particularly harsh are significantly shorter two years after the shock. The negative effect of the shock is strongest for children from herding households. Moreover, we explore the role of mitigation channels to cushion the impact of the weather shock. In households where the head has more experience in herding, children suffer less from the consequences of the shock. Similarly, households having access to alternative sources of income are better able to protect their children from the effect of the shock. Finally, both the amount of emergency aid delivered per district and the presence of an international organization in a given district relieve the negative impact of the shock. Our findings are robust to different measures of shock intensity and to endogenous migration.
Keywords: I10; O12; J13; 330